(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
Both organic and chemical fertilizers play a vital role in enhancing crop productivity and maintaining soil health. However, inflated prices of chemical fertilizers also reduced their rate of application, hence, reducing crop productivity in Ethiopia. Therefore, to sustain the productivity of lands and crops, there is an urgent need to promote the use of organic fertilizers. Vermicomposting is one method of preparing enriched compost with the use of earthworms. With the support of the second phase of the Agricultural Growth Program (AGP-II), the introduction and promotion of vermicomposting technology were conducted. However, the production status and role of vermicomposting for smallholder farmers in the area are unclear. Therefore documenting the achievement and progress of vermicomposting is necessary. Both primary and secondary data (2018-2021) were collected by using snowball sampling techniques. The descriptive statistics reveal that in addition to potato production, farmers are using vermicompost for chat, enset, coffee, forage and vegetable production. Accordingly, the production, utilization, and sale trend of vermicompost increased from 2018 to 2021. In addition, vermicomposting created an opportunity for farmers to participate in earthworms and vermicompost selling. Due to this, those who had vermicompost in their home garden do not use inorganic fertilizers for any crop production during the last four years. In addition, the average cultivated cropland coverage by vermicompost-based production also increased from 2018 to 2021. Its preparation procedure is also consistent with the manual provided to them. Therefore expanding vermicomposting technology in the area has the potential to enhance sustainable crop and land productivity. Int. J. Agril. Res. Innov. Tech. 12(2): 88-95, December 2022